Take-up and demand for a bundle of biofortified seeds and agricultural inputs in northeastern Nigeria - Amare, Mulubrhan; Ambler, Kate; Bamiwuye, Temilolu; Bloem, Jeffrey R.; Misra, Rewa S.; Wagner, Julia (International Food Policy Research Institute, 2024)
Smallholder farmers in northeastern Nigeria face interrelated challenges of food insecurity, climate volatility, and conflict. Northeastern Nigeria has some of the highest levels of food insecurity in Nigeria (UNICEF, 2023), and more volatile rainy seasons have led to massive floods, depleted soil quality, and disrupted agricultural growing seasons. The changing climate, therefore, presents challenges for improving agricultural productivity and addressing food insecurity. Additionally, millions in the region have fled their homes due to conflict between pastoralist livestock herders and settled agricultural communities over land use and extremism (International Crisis Group, 2023; McGuirk and Nunn, 2023). Exposure to conflict itself contributes to reduced agricultural production (Adelaja and George, 2019) and increased food insecurity (George et al., 2020). Studies also indicate a decade-long increase in conflict levels, where poverty is associated with sustained conflicts. Northeast Nigeria is notably affected, with 49 per cent of households experiencing conflict between 2010 and 2017 (Azad et al., 2018).